Exploring student satisfaction and perceived employability: a quest for the quality of polytechnics as perceived by students - Ghozi, Saiful; Utami, Hamidah Nayati; Kusumawati, Andriani; Yulianto, Edy (Millenium - Journal of Education, Technologies, and Health, 2025)
Introduction: Student satisfaction and perceived employability are critical constructs in assessing perceived quality of higher education institutions, and thus exploring them has been the focus of extensive research. Objective: Explore student satisfaction and perceived employability in Indonesian higher vocational education, namely polytechnics. Methods: Convergent-parallel mixed methods approach. The data was collected from 356 final-year students enrolled in four-year diploma programs across four state polytechnics in East Java, Indonesia. In the quantitative strand, closed-ended responses were analyzed descriptively using tertile analysis and inferentially through Kruskal–Wallis, Mann–Whitney U, and Spearman’s correlation tests. Results: Student satisfaction and perceived employability levels are consistent across demographic groups, with a significant positive correlation found between these two constructs. Three overarching factors contributing to student satisfaction are academics, non-academics, and employability. Two overarching factors contributing to perceived employability are internal employability and external employability. The academic factor, particularly curriculum design and faculty competence, emerges as the main determinant of student satisfaction. The internal employability factor—understood as what is offered to employers—appears more influential in shaping perceived employability than the external employability factor—understood as what employers expect. Conclusion: The study offers theoretical contributions and practical recommendations to improve the perceived quality of polytechnics, aligning educational outcomes with the expectations of students, parents, and industry stakeholders.